2010
DOI: 10.1111/j.1540-6520.2009.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Export Propensity

Abstract: This article draws on theories about the internationalization process of small-and mediumsized enterprises (SMEs) and feminist arguments to explain gender differences in export propensity. Findings are based on a large-scale survey of Canadian SMEs. After controlling for sector, firm, and owner attributes, female majority-owned firms were significantly less likely to export than firms owned by men. The implications for entrepreneurship and feminist theory, export policy, and research are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
4
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 56 publications
(121 reference statements)
6
125
4
9
Order By: Relevance
“…Other studies (e.g., Orser et al, 2010;Marques, 2015) have suggested that different export propensity between firms led by women and men may be a reason for the gender gap. Chen, Leung, and Evans (2015), among others, indicated that the innovative potential of a firm and the propensity to invest in research and development and introduce innovation may be affected by the gender composition of ownership and management.…”
Section: The Literature On Gender Gap and Firm Productivitymentioning
confidence: 99%
“…Other studies (e.g., Orser et al, 2010;Marques, 2015) have suggested that different export propensity between firms led by women and men may be a reason for the gender gap. Chen, Leung, and Evans (2015), among others, indicated that the innovative potential of a firm and the propensity to invest in research and development and introduce innovation may be affected by the gender composition of ownership and management.…”
Section: The Literature On Gender Gap and Firm Productivitymentioning
confidence: 99%
“…The sampled entrepreneurial ventures report, on average, 4.09 employees, and the new businesses in their first two years of operations show a significantly lower employment level (3.25 employees), compared to businesses with more years in the market (4.26 employees) (Table 2). A set of variables associated with the entrepreneur's profile was included: a dummy variable for gender (one for male, and zero otherwise) (Orser et al 2010), age of the individual expressed in years (Lee et al 2016) and a set of dummy variables accounting for the different levels of education attainment (primary studies, secondary studies, and post-secondary studies) (Suzuki et al 2017). To account for the differences in the internationalization patterns of businesses across industries (Javalgi et al 2000), we introduce three dummy variables that group businesses in three wide industry categories: manufacturing, business services and consumer services sectors.…”
Section: Control Variablesmentioning
confidence: 99%
“…En 2011, 5% seulement des PME à contrôle majoritaire féminin exportaient, contre 12 % de celles à contrôle majoritaire masculin (Industrie Canada, 2015). Même après avoir contrôlé pour les caractéristiques des secteurs, des entreprises et des propriétaires, les PME détenues par des hommes ont davantage tendance à exporter (Orser et al, 2010). En réduisant ces écarts, on ferait progresser la productivité et l'inclusion sociale (ne serait-ce que parce que les femmes sont surreprésentées dans l'entrepreneuriat social et les activités innovantes qui cherchent à satisfaire les besoins des communautés locales et de la société).…”
Section: Développer L'entrepreneuriat Fémininunclassified